The Age of Contentment: Exploring Happiness through Generational Lenses in Pakistan - Sharif , Abida; Sadaf, Fouzia; Sohail, Hareem (Pakistan Journal of Humanities and Social Sciences, 2023)
This study provides a comprehensive sociological exploration of happiness among older adults in Pakistan, drawing on a diverse array of socio-cultural factors. Utilizing a mixed-method approach that combines in-depth interviews and thematic analysis, the research investigates the multifaceted dimensions of happiness, with particular emphasis on the satisfaction with meeting physiological demands, the generational shift from collectiveness to individuality, the role of social support and family, and a comparative analysis with the younger generation's perspectives. Key findings reveal the paramount importance of good health and basic health facilities in achieving happiness, with close family ties and economic stability acting as significant contributors. The intricate interplay between joint and nuclear family structures sheds light on the complex dynamics of personal freedom, independence, and the value of positive relations within the family. The study further uncovers the linkage between educational achievements and happiness, portraying a cohesive picture that aligns with broader societal values and norms. Cultural reflections unveil a specific understanding of happiness within the Pakistani context, highlighting the nuanced interactions between traditional values and modern aspirations. The findings offer profound implications for policymakers, educational institutions, and communities, emphasizing the need to foster supportive environments, nurture social connections, and understand the evolving nature of social relations within a rapidly changing society. Overall, the research contributes a rich and nuanced understanding of happiness, resonating with universal themes while deeply rooted in the specific socio-cultural landscape of Pakistan.